Investigation of periodic structures in gas-liquid flow - Alamu, Mhunir Bayonle (2010)
Three different experimental campaigns had been launched to investigate the periodicity of the two-phase flow structures like the void waves in bubbly flow, liquid slugs and Taylor bubbles in slug flow, huge waves in chum flow, disturbance waves in annular flow and wisps in wispy-annular flow. The three experiments and data analysis had been considered in increasing order of complexity. Time varying data were acquired in all the three campaigns. At the simplest level of analysis statistical measures were extracted from the time series, presented, discussed and conclusions drawn.